Sixtiers (1964–1974) - Antipin, Lyutsian; Berzhinsky, Yurii; Dagdanova, Tsyredar; Nechitailo, Vladimir (project baikal, 2015)
Irkutskgrazhdanproject was founded in the middle of the 1960s, a unique and wonderful time. Clear and heavy forms of Neo-Brutalism matched harmoniously the context of the Siberian city of Irkutsk. Young architects of the western avant-garde were aligned with the emerging Irkutsk school, which was unexpected, because both parties could hardly know about each other. But it is obvious that the first architects from Irkutskgrazhdanproject ranged among such great architects as the Smithsons, Louis Kahn and Kenzo Tange.